Utilização de enzimas pectolíticas no processamento de suco de maracujá integral (Passiflora edulis f. flavicarpa Den.) - Guimarães, Antonio Claudio Lima (1985)
In order to accomplish this work we. used yellow passion fruit (Passiflora edulis f. flavicarpa Deg.) from Ibiapaba plateau (Serra Grande) in Ubajara county, State of Ceara-Brazil. [...]